Editorial - Van Damme, Patrick (Afrika Focus, 2017)
This issue of Afrika Focus has 3 contributions on what might be termed domesti- cation and propagation of lesser known tree species from Central Africa. Gnetum africanum is a rich source of leaves that has become somewhat overharvested and is therefore threatened in its natural distribution environment. Dacryodes is an interesting fruit species that can easily be integrated into existing agroforestry systems in order to make the latter more resilient, and also provide a richer source of vitamins and proteins. Garcinia has medicinal value and is thus a profitable source of income for those farmers who grow it. A fourth article deals with the socio-economics of land tenure in a largely agricultural area in Cameroon. Recent economic development is exerting pressure on the people and their production environment, thus making secure rights over land a critical issue.